ANALISIS SUSEPTIBILITAS MAGNETIK BATUAN ULTRABASA DI AREA PASCA TAMBANG PADA WILAYAH KECAMATAN POMALAA KABUPATEN KOLAKA PROVINSI SULAWESI TENGGARA - ilma septia ningsi (Jurnal Rekayasa Geofisika Indonesia, 2020)
An analysis of the magnetic susceptibility of ultramafic rocks in the post-mining area of Pomalaa Sub-district, Kolaka Regency, Southeast Sulawesi Province has been carried out using Magnetic Susceptibility Method. This research is used to determine the magnetic susceptibility of ultramafic rocks in Pomalaa District, to determine the types of magnetic minerals contained in ultramafic  rocks based on magnetic susceptibility data   magnetic field and determine the type of  ultramafic rock   with  magnetic  susceptibility. The   tools  used   are  MS2B   Bartingtong suseptibility meters and X-Ray Difraction (XRD).The magnetic susceptibility value of ultramafic rocks in Pomalaa District is 172 x 10-5 SI to 2789.6 x 10-5 SI, the type of minerals in the dominant ultramafic rocks is hematite (αFe2O3), whereas for ultramafic rock types in Pomalaa District, they are serpentinite with magnetic susceptibility value 2592 x 10-5 SI and harzburgite with magnetic susceptibility value 449,2 x 10-5 SI. Key words: Magnetic susceptibility analysis, ultrabasa, MS2B bartingtong